Deep-profiling of phospholipidome via rapid orthogonal separations and isomer-resolved mass spectrometry - Xia, Tian; Zhou, Feng; Zhang, Donghui; Jin, Xue; Shi, Hengxue; Yin, Hang; Gong, Yanqing; Xia, Yu (Nature communications, 2023)
A lipidome comprises thousands of lipid species, many of which are isomers and isobars. Liquid chromatography-tandem mass spectrometry (LC-MS/MS), although widely used for lipidomic profiling, faces challenges in differentiating lipid isomers. Herein, we address this issue by leveraging the orthogonal separation capabilities of hydrophilic interaction liquid chromatography (HILIC) and trapped ion mobility spectrometry (TIMS). We further integrate isomer-resolved MS/MS methods onto HILIC-TIMS, which enable pinpointing double bond locations in phospholipids and sn -positions in phosphatidylcholine. This system profiles phospholipids at multiple structural levels with short analysis time (<10 min per LC run), high sensitivity (nM detection limit), and wide coverage, while data analysis is streamlined using a home-developed software, LipidNovelist. Notably, compared to our previous report, the system doubles the coverage of phospholipids in bovine liver and reveals uncanonical desaturation pathways in RAW 264.7 macrophages. Relative quantitation of the double bond location isomers of phospholipids and the sn -position isomers of phosphatidylcholine enables the phenotyping of human bladder cancer tissue relative to normal control, which would be otherwise indistinguishable by traditional profiling methods. Our research offers a comprehensive solution for lipidomic profiling and highlights the critical role of isomer analysis in studying lipid metabolism in both healthy and diseased states. The existence of large number of isomers poses challenges for lipidomic analysis. The authors integrate hydrophilic interaction liquid chromatography, trapped ion mobility, and isomer-resolved MS/MS into a single system, enabling deep profiling of phospholipidomes at fast speed and wide coverage.